The technique of ctrl + c and ctrl + v: a study on the practice of plagiarism in the academic environment between students of a brazilian university (Research, Society and Development, 2019)
The objective of this study is to verify how the technique of replication of works by "Ctrl + c" and "Crtl + v" is applied in the academic environment by university students of a Brazilian university, the main reasons for this practice, as well as the view of the students this problematic that has been causing great discussion in academic circles due to the ethical and authorial issues involved. For the analysis procedure, a study of the anti-graft law was carried out. In addition, an investigation was carried out on how technology has contributed to the practice of plagiarism among students of a Brazilian university. The technique used was a survey type. The results show that most of the students have knowledge about plagiarism and techniques to avoid it. However, many students have already reported plagiarism at university. In this perspective, it was emphasized that there should be a greater presence of debate on the ethical issues surrounding the act of plagiarism, seeking to minimize this act in the academic environment. There is also a need for universities to apply legal punishments to plagiarists.